The aims of humanities in the training of medical students on the example of history subjects - V. I. Chumakov (Кардиоваскулярная терапия и профилактика)
The article is devoted to the study of the place of history subjects in the formation of general cultural competencies of medical students. A theoretical analysis of the topic in domestic and foreign history and pedagogical science has been carried out. The necessity of history subjects in the system of higher professional medical education is substantiated. Based on many years of experience, pedagogical technologies developed by the authors are presented that most fully form general cultural and professional competencies within historical subjects. The data of pedagogical research on the topic are given, the opinions of students on the content of history subjects, on the process of forming knowledge, skills and abilities of medical students are explicated. The practical significance of the study for improving the pedagogical process in a medical university is reflected.